2021
DOI: 10.1002/jhbp.1068
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel surgical difficulty grading system during laparoscopic cholecystectomy

Abstract: Background: Prevention of bile duct injury and vasculo-biliary injury while performing laparoscopic cholecystectomy (LC) is an unsolved problem. Clarifying the surgical difficulty using intraoperative findings can greatly contribute to the pursuit of best practices for acute cholecystitis. In this study, multiple evaluators assessed surgical difficulty items in unedited videos and then constructed a proposed surgical difficulty grading. Methods:We previously assembled a library of typical video clips of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…The TG18 difficulty score includes detailed grading of findings related to AC. The objectivity and universality of this difficulty score has been demonstrated by Asai et al 9 and furthermore, in our study, this difficulty score was shown to correlate appropriately with surgical outcomes. It therefore allows for comparisons among different institutions and studies and facilitates investigation of preoperative risk factors for difficult surgeries as well as the relationship between surgical difficulty and postoperative complications.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The TG18 difficulty score includes detailed grading of findings related to AC. The objectivity and universality of this difficulty score has been demonstrated by Asai et al 9 and furthermore, in our study, this difficulty score was shown to correlate appropriately with surgical outcomes. It therefore allows for comparisons among different institutions and studies and facilitates investigation of preoperative risk factors for difficult surgeries as well as the relationship between surgical difficulty and postoperative complications.…”
Section: Discussionsupporting
confidence: 86%
“…No patients had a difficulty score of 6 in this study. Each of the median, highest, and mean score were classified into three grades: grade A (zero to one point), grade B (two to four points), and grade C (five to six points) according to report by Asai et al 9 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations